Hypertension and its correlation with renal lesions in dogs with leishmaniosis - Braga, Eveline Tozzi [UNESP]; Artero de Carvalho Leite, Joao Henrique [UNESP]; Rosa, Fernando Azadinho [UNESP]; Tivelli, Patricia [UNESP]; Araujo, Amanda Mariano [UNESP]; Martins de Almeida, Breno Fernando [UNESP]; Ferrari, Heitor Flavio [UNESP]; Ciarlini, Paulo Cesar [UNESP]; Machado, Gisele Fabrino [UNESP]; Marcondes, Mary [UNESP] (Brazilian Coll Veterinary Parasitology, 2015)
To evaluate the prevalence of hypertension and its correlation with the severity of renal injury and proteinuria in dogs with leishmaniosis, sixty-six dogs were divided into two groups. Group 1 (G1) was composed of 54 dogs included in stage 1 of chronic kidney disease (CKD), and group 2 (G2) of twelve dogs in stages 2 and 3 of CKD. Prevalence of hypertension was 28.8%, comprising 22.2% of the dogs from G1 and 58.3% from G2 (P=0.011). The mean arterial blood pressure (BP) of dogs from G1 (135.7 +/- 20.5) was lower than from G2 (170.0 +/- 26.3) (P <0.001). Urine proteincreatinine ratio (UP/C) revealed values above 0.5 in 75.7% of the dogs, with 34% presenting hypertension. All dogs with hypertension had histopathological and laboratory evidence of glomerular disease. Although there was no statistically significant correlation between elevated BP and the severity of glomerular lesions (P=0.408), there was a statistically significant correlation between elevated BP and increased UP/C in the studied population (P=0.002). Thus, dogs with leishmaniosis and renal disease must be screened for the presence of hypertension so that treatment may be instituted as early as possible, in countries where treatment is allowed, to prevent the progression of renal damage.

Para avaliar a prevalência de hipertensão arterial e sua correlação com a severidade da lesão renal e proteinúria em cães com leishmaniose, 66 cães foram divididos em dois grupos. O grupo 1 (G1), composto por 54 cães em estágio 1 de doença renal crônica (DRC), e o grupo 2 (G2) por 12 cães em estágios 2 e 3 de DRC. A prevalência de hipertensão foi de 28,8%, compreendendo 22,2% dos cães de G1 e 58,3% dos cães de G2 (p = 0,011). A pressão arterial média (PA) de G1 (135,7 ± 20,5) foi inferior a de G2 (170,0 ± 26,3) (P <0,001). A relação proteína creatinina urinária (P/C U) foi maior que 0,5 em 75,7% dos cães, dos quais 34% possuíam hipertensão. Todos os cães com hipertensão apresentavam doença glomerular. Embora não tenha sido observada correlação estatisticamente significativa entre elevação da PA e severidade das lesões glomerulares (P =0,408), houve uma correlação significativa entre PA elevada e aumento da UP/C (P = 0,002). Portanto, cães com leishmaniose e doença renal devem ser pesquisados ​​quanto à presença de hipertensão, para que o tratamento possa ser instituído o mais precocemente possível em países onde ele é permitido, para evitar a progressão da lesão renal.
Hipertensão e sua correlação com lesões renais em cães com leishmaniose
Keywords: Histopathology; Kidney; Leishmania infantum chagasi; Systolic blood pressure; Histopatologia; Rim; Leishmania infantum chagasi; Pressão arterial sistólica